New guard - Muchamore, Robert (London : Hodder Children's Books, 2017)
Ryan Sharma is a CHERUB agent. Working undercover, he can slip under adult radar and get information that sends criminals and terrorists to jail. Now he's investigating a double kidnapping, working with mission controller and old guard, James Adams. In the mission to end all missions, Ryan and James must assemble a team of legendary CHERUB agents to find the hostages and bring them home.
Young Adult
Young Adult
Keywords: Kidnapping -- Juvenile fiction; Undercover operations -- Juvenile fiction; Kidnapping -- Fiction; Undercover operations -- Fiction; Criminal investigation -- Fiction; Kidnapping -- Fiction; Action and adventure fiction; Spy fiction